Route Selection and Trajectory Filling in Mobility Traces - Domingues, Augusto C. S. A.; Loureiro, Antonio A. F.; Silva, Fabrício A. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2019)
The feasibility of vehicular networks is directly related to the understanding of mobility patterns, which is a necessary knowledge for the elaboration and application of novel algorithms and technologies for such networks. However, there are few traces that represent urban mobility with details and precision. The main objective of this dissertation is to characterize the mobility of vehicles in urban environments and to use this information to propose an algorithm to generate and enrich data in this environment.